PTU-006 Incidence of immune check point inhibitor induced diarrhoea/colitis- experience from a multi-centre cohort. (8th June 2018) - Spain, Lavinia; Samani, Amit; Ibraheim, Hajir; Au, Lewis; Tippu, Zayd; Zhang, Shuai; Merrick, Sophie; Josephs, Debra; Fazal, Waqas; Papa, Sophie; Powell, Nick; Yousaf, Nadia; et al.
Abstract : Background: Immune checkpoint inhibitors (ICIs) including anti-CLTA-4 (e.g. ipilimumab (ipi)) and anti-PD-1 antibodies (e.g. nivolumab (nivo)) have improved outcomes in many cancers. However their use is complicated by ICI-related diarrhoea/colitis (irD/C), a common cause of morbidity and ICI discontinuation. The National Cancer Institute's Common Terminology Criteria for Adverse Events (CTCAE) has been used to grade irD/C according to frequency of bowel movements over baseline. Grade 1–2 represents mild-moderate disease, grade 3–4 severe disease and grade 5 represents death. In clinical trials diarrhoea/colitis is more common in regimes using anti-CTLA-4 agents. 1 There are few real world data reported in the UK. Methods: Electronic medical records were reviewed for melanoma patients (pts) at The Royal Marsden Hospital (RMH) and melanoma, renal and lung cancer pts Guy's and St Thomas' Hospital (GSTT), receiving at least one ICI dose between 2011–2016. Clinical outcome data included class of ICI therapy and CTCAE grade of diarrhoea. Results: 651 ICI treatment courses were administered mostly for melanoma (100% RMH, 53% GSTT). 285 (44%) received anti-CTLA-4 monotherapy, 288 (44%) anti-PD-1 monotherapy, and 77 (12%) combination ipi +nivo. The incidence of all-grade irD/C was 27% for anti-CTLA-4 therapy, 12% for anti-PD-1%–34% for ipi +nivo. The incidence of severe irD/C (grade 3–5) was 12% in anti-CTLA-4 monotherapy, 4% in anti-PD-1 therapy and 26% in combination therapy (figure 1). There was one only death reported in a pt who developed colitis following treatment with anti-CTLA-4 monotherapy. Conclusion: This is the largest cohort of data reporting the incidence of irD/C involving real-world patients. Compared to trial data, the incidence of all-grade diarrhoea was slightly lower but the incidence of severe disease was higher in all treatment groups, particularly with ipi +nivo. Given the expansion of ICIs in other cancer types and use as an adjuvant therapy, there is an urgent need to engage gastroenterology services and to develop evidence-based management algorithms for treatment of irD/C. Reference: . Spain L, Diem S, Larkin J. Management of toxicities of immune checkpoint inhibitors. Cancer Treat Rev2016;44:51–60.